2019
DOI: 10.1038/s41598-018-38270-3
|View full text |Cite
|
Sign up to set email alerts
|

Using DNA Barcoding to Investigate Patterns of Species Utilisation in UK Shark Products Reveals Threatened Species on Sale

Abstract: Many shark populations are in decline, primarily due to overexploitation. In response, conservation measures have been applied at differing scales, often severely restricting sales of declining species. Therefore, DNA barcoding was used to investigate sales of shark products in fishmongers and fish and chip takeaways in England. The majority of samples were identified as Spiny Dogfish (Squalus acanthias), which is critically endangered in the Northeast Atlantic and landings have been prohibited (although there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…Research has revealed that spiny dogfish and small-spotted catshark are regularly sold in fish and chip shops under pseudonyms such as "Rock", "Rock salmon" and "Murgey" 110 . If contaminants are able to pass from the digestive tract to the muscle tissue of these shark species, then humans may inadvertently be consuming these pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that spiny dogfish and small-spotted catshark are regularly sold in fish and chip shops under pseudonyms such as "Rock", "Rock salmon" and "Murgey" 110 . If contaminants are able to pass from the digestive tract to the muscle tissue of these shark species, then humans may inadvertently be consuming these pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Ukraine 7Cote d'Ivoire (7) Belarus (6) Turkey (9) Belgium 8Angola (10) New Zealand (8) Mauritius 10Russia 12Peru 2Chile (5) Morocco (9) Myanmar (0) Viet Nam 1Unknown 29Philippines 3India 13USA (33) Mexico 8Taiwan (15) Turkey (8) Belize 5China (13) Indonesia 2Japan (21) Norway 8Thailand 1Malaysia 3Canada 11Spain (43) South Korea (24) Ireland 12UK (27) Senegal (16) Portugal (39) Ukraine (19) Iceland (8) Mauritania 5Netherlands 11France 32 industrial fishing data to determine how much and which type of threatened species are reported in catch records and by whom; information critical for focusing conservation and management action towards threatened marine fish and invertebrates. We present the most conservative estimate of catch volumes of threatened seafood species by excluding unreported catch, records from non-industrial sectors (which are often not reported to the FAO), or catch reported in aggregated commodity groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, consumers should be able to purchase seafood that is from a well-managed stock that is secure on a global scale, consistent with World Trade Organization measures relating to the conservation of exhaustible natural resources, international fisheries agreements such as the UN Fish Stocks Agreement, and global targets for biodiversity such as the UN Sustainable Development Goal 15 23,38 . Some distinct populations of globally threatened species may be fished sustainably, but the current structure of the seafood supply chain makes it difficult for consumers to make informed, sustainable purchases 38,39 . A crucial first step to better management of fishing pressure on threatened marine species is better taxonomic resolution of catch and trade data, so that we can more accurately understand what species we are catching and consuming and their conservation statuses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Isurus oxyrinchus to replace Prionace glauca in this study could be from unreported and unregulated illegal (IUU) fishing landed at Italian ports. In fact, mislabeling of fish products is used either to launder IUU fish into the legal marketplace or else simply to defraud the industry and consumer in order to garner a higher sale price [5,9]. Further, among the samples labeled as palombo, the over-exploitation in the Mediterranean Sea of M. mustelus, currently classified as vulnerable on the IUCN Red List [12], could justify the species' non-identification [15,76].…”
Section: Discussionmentioning
confidence: 99%
“…Sharks are fish of great commercial importance, highly appreciated and widely consumed in many countries [ 1 ]. Although a large number of shark products, such as fins, cartilage, leather, liver oil, jaws and teeth, are already being widely traded [ 2 , 3 , 4 ], the global shark meat market looks set to grow in future years, with shark meat products commercialized in various forms, such as whole, fresh or frozen, tails, slices, fillets or minced, smoked, salted and dried meat [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%